USE OF URINARY CATHETERS FOR CLEAN INTERMITTENT CATHETERIZATION: SATISFACTION OF PATIENTS WITH BONE MARROW INJURY - Gisela Maria Assis; Aline Fernanda Negri; Sabrina Alves Veiga Tung; Camila Francine Galli Saccomani; Auristela Duarte de Lima Moser; Gisele Regina de Azevedo; Gislaine de Melo Meira (Universidade Federal do Paraná, 2015)
The objective in this study was to assess the use of the conventional catheter, hydrophilic catheter and pre-lubricated catheter with bag for clean intermittent catheterization. Exploratory-descriptive cross-sectional research involving 59 bone marrow injury patients attended at rehabilitation centers of three Brazilian states between January and April 2012. The questionnaire to assess the perceived catheter attributes and the adapted consumption experience satisfaction questionnaire were used. The conventional catheter was not statistically superior in any aspect assessed. The hydrophilic catheter was considered superior to the conventional for package opening and sliding during insertion. The pre-lubricated catheter with bag was superior to the conventional for package opening, introduction, sliding and removal. The indication of the ideal catheter depends on the individual assessment of the patients, their difficulties, potentials and preferences.